The Prevalence of Hypertension and its Related Factors in Children Aged 7 to 12 Years in Larestan (South Fars Province, Iran) - Ziba Moravej; Gholamali Haghighat; Aboubakr Jafarnezhad; Atefeh Raoufi; Sanaz Atef; Azizallah Dehghan (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Childhood hypertension can have serious consequences for children, especially during their adulthood. This study aimed to determine the prevalence of hypertension and its related factors in children aged 7 to 12 years in Larestan (Iran). Methods: In this cross-sectional study, 1110 students from 7 to 12 years old in Larestan were enrolled in the study using cluster sampling. In order to collect educational data, 10 girls' primary schools and 10 boys' primary schools were randomly selected from all the girls' and boys' primary schools. Then, considering that each school has different number of students, 55 students of each school were randomly selected. Students' blood pressure was measured as standard. Their personal information was also recorded in a checklist. A checklist containing demographic information, factors and variables that affect the prevalence of hypertension in children aged 7 to 12 years was used. To collect information, a checklist was used that included demographic information such as age, gender, and place of residence. Also, in order to identify factors and variables effective in the prevalence of high blood pressure (HBP), tools such as sphygmomanometer and other risk factors including obesity, type of diet, physical activities, and body mass index (BMI) were used. Results: The mean age of girls was 9.11 ± 1.53 and boys were 9.19 ± 1.52, which did not differ significantly from the statistical point of view. The prevalence of pre hypertension was 6.03% (95% CI: 4.71-7.60) and the prevalence of hypertension was 4.14% (95% CI: 3.05-5.49). Systolic and diastolic blood pressure has direct relation with height and weight of children. Diastolic blood pressure also had a higher prevalence in girls (P < 0.001). Conclusion: Overweight and obesity as a moderate aggressive factor were significantly associated with blood pressure. Also, the prevalence of HBP in children was significant, and it is necessary to pay attention to it in childhood. Moreover, hypertension cases should be identified and treatment should start faster for the affected person to prevent the adverse consequences in the future.